Pengaruh Jarak Psikologis Sosial dan Upaya Kognitif terhadap Niat Membeli Produk Fashion Uniqlo dengan Mediasi Nilai yang Dirasakan - Rasheesa Reegia Aulia Putri; Soepatini (El-Mal: Jurnal Kajian Ekonomi & Bisnis Islam, 2025)
This study aims to analyze the influence of social psychological distance and cognitive effort on the purchase intention of Uniqlo fashion products on Instagram, with perceived value as a mediating variable. A quantitative approach was employed, involving 132 respondents selected through purposive sampling. Data analysis was conducted using Partial Least Squares (PLS) with SmartPLS 3.0. The results show that social psychological distance and cognitive effort have a significant positive effect on perceived value and purchase intention. Perceived value also has a positive effect on purchase intention. However, perceived value does not significantly mediate the relationship between social psychological distance and cognitive effort and purchase intention. This study contributes to the digital marketing literature by identifying the role of psychological and cognitive perceptions in online fashion purchasing behavior.